Advancing Sustainability through Urban Green Space: Cultural Ecosystem Services, Equity, and Social Determinants of Health - Jennings, Viniece (Int J Environ Res Public Health, 2016)
Urban green spaces provide an array of benefits, or ecosystem services, that support our physical, psychological, and social health. In many cases, however, these benefits are not equitably distributed across diverse urban populations. In this paper, we explore relationships between cultural ecosystem services provided by urban green space and the social determinants of health outlined in the United States Healthy People 2020 initiative. Specifically, we: (1) explore connections between cultural ecosystem services and social determinants of health; (2) examine cultural ecosystem services as nature-based health amenities to promote social equity; and (3) recommend areas for future research examining links between urban green space and public health within the context of environmental justice.